Studi Komparatif Resiliensi Akademik pada Mahasiswa Rantau dan Mahasiswa Non-rantau - Nindya Wahyu Hening Andjanie; Riza Noviana Khoirunnisa (Yayasan Literasi Sains Indonesia, 2026)
Current students face academic pressure, social challenges, and academic problems in higher education due to the presence of artificial intelligence technology. This study aims to determine the significance of differences in academic resilience levels between students living away from their families and students living with their families. A quantitative comparative design approach was used in this study, involving 168 students selected using purposive sampling. Data were collected through an academic resilience scale and then analyzed using the Independent Sample T-Test to observe differences in academic resilience between students living away from their families and students living with their families. The results showed no significant difference in academic resilience between students living away from their families and students living with their families (p = 0.359, p > 0.05). Overall, these findings confirm that both students living away from their families and students living with their families are able to develop academic resilience through different adjustment mechanisms but with relatively equal levels of ability. The practical implications of this research are expected to assist educational institutions in designing policies and services to optimize academic resilience capabilities for all students in an inclusive and accessible manner.